Rancangan Simulasi Inverter 7 - Tingkat Tipe Flying Capacitor untuk Aplikasi PLTS Mandiri Energi Bersih Dan Terbarukan - Tjokro, Christoper (ReTII, 2018)
Limitations of the voltage rating was the main issue in high voltage power conversion. By applying multicell inverters, it is possible to synthesize a high voltage waveform from multiple voltages. In this case is designed a simulated flying capacitor, seven level inverter which will be furthered used in a photovoltaic energy generation system as an alternative in energy source. In a photovoltaic generation system, the main components are the PV, MPPT, and the inverter. As conventionally designed, the inverter of the system uses the conventional method of Half â€“ bridge type inverter which has a relatively high harmonic distortion in its waveform.What will be further discussed is the flying capacitor, seven level inverter. The seven level inverter has higher stability and lower harmonic distortion in its output waveform, Asin real application the harmonic distortion of an output waveformshould be below 5% for an allowed and recommended general application use. By this project, the total output harmonic distortion of this seven level inverter is 3,83%. The data that would be the reference for this paper is the data from the simulated design of the flying capacitor, seven level inverter using the Power Simulater software. Asit will be mentioned later on in the paper, there will be a brief explanation of the MPPT that would be used to boost the DC photovoltaic source to a desired value and a more detailed explanation in the inverter design to supply an AC source that could be later used in general purposes. Â  Keywords: Multilevel Inverter,Photovoltaic, Power Supply